PERSEPSI PEDAGANG SETELAH PEMBANGUNAN PASAR BELIMBING PADANG - elsa mayang sari; Afdhal Afdhal (JURNAL BUANA, 2021)
Abstract This study aims to determine the responses of traders after the development of the Padang starfruit market which includes knowledge of traders 'perceptions and traders' views about market facilities. This type of research is descriptive quantitative. The population of this study were all traders in the star fruit market, as many as 540 traders. The sample in this study were as many as 85 traders. The technique of collecting data using a questionnaire. Data analysis techniques with percentages. The results showed that: the traders' perceptions of the construction of the Belimbing market in Kuranji district stated that they agreed that the building was located in the middle of a residential area so that it was easily accessible to all residents who were around the market and launched buying and selling transactions. Meanwhile, the market facilities after the development of the Belimbing Padang market in Kuranji sub-district have not been implemented properly.